O’SPEAK FOR ENGLISH PHONETIC AND PHONOLOGY CLASS: WHAT’S ON STUDENTS’ MIND? - Candradewi Wahyu Anggraeni; Widya Ratna Kusumaningrum; Rangga Asmara (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2021)
In the era of Education 5.0, mobile applications for the teaching-learning process are proliferating. The mobile application also exists in English Phonetics and Phonology Classes. Its name is O’Speak. The use of O’Speak in English Phonetic and Phonology Class derives from the idea of technological development in this digital era. Virtues and hurdles of using O’Speak come out in students’ viewpoints. Therefore, this study is conducted to know the students’ perceptions toward the use of O’Speak in English Phonetic and Phonology Classes. The research method used in this study is a case study that focuses on the phenomenon of O’Speak. English Phonetics and Phonology students are the participants in this study. The finding shows that the students have several overviews toward O’Speak, such as students' concept of O’Speak, O’Speak designs, and O’Speak comments.